Assessing Public Expenditure on Health from a Fiscal Space Perspective - Tandon, Ajay; Cashin, Cheryl (World Bank, Washington, DC, 2013)
This document delineates a simple conceptual framework for assessing fiscal space for health and provides an illustrative roadmap for guiding such assessments. The roadmap draws on lessons learned from analyses of seven fiscal space case studies conducted over the past two years in Cambodia, India, Indonesia, Rwanda, Tonga, Uganda, and Ukraine. The document also includes a summary of the fiscal space assessments from these seven case studies. Any assessment of fiscal space typically entails an examination of whether and how a government could feasibly increase its expenditure in the short-to-medium term, and do so in a way that is consistent with a country's macroeconomic fundamentals. Although fiscal space generally refers to overall government expenditure, for a variety of reasons there has been growing demand for a framework for analyzing fiscal space specifically for the health sector. This document outlines ways in which generalized fiscal space assessments could be adapted to take a more health-sector specific perspective: what is the impact of broader macroeconomic factors on government expenditures for health? Are there sector-specific considerations that might expand the set of possible options for generating fiscal space for health? Are there country-specific examples of innovative strategies that have been successful in increasing fiscal space for health?